Quasars and black holes - World Book, Inc (Chicago, IL World Book, 2010)
An introduction to quasars and black holes with information about their formation and characteristics. Includes diagrams, fun facts, a glossary, a resource list, and an index"--Provided by publisher
Includes index
Hurg
5 8
Keywords: Black holes -- Juvenile literature; Quasars -- Juvenile literature